Analysis of Overhead Costs Management in Companies - Wolfram Irsa; Csaba Székely (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2021)
The development of overhead costs management is becoming more and more important as the percentage of overhead costs is rising. The last 15 years have demonstrated the awakening of advanced methods and tools aimed at understanding the utilization of overheads better. The paper investigates the current state of overhead costs management using a sample of 20 companies in Austria, Hungary, and Slovakia. A qualitative approach was applied in a multi-case study, which unveiled the significance of overhead cost management with the increasing trend of importance. The effort reflects current innovations using digitalization of processes. The findings show that (1) the majority of the companies indicated that digitalization heavily impacts overhead costs; (2) all expressed their dissatisfaction with the tools currently used; and (3) the majority cited that usability and speed are the predominant factors. The analysis and the subsequent synthesis delivered three theses: (1) perception that digital competence enables overhead costs management; (2) belief that competencies are insufficient; and (3) there are prerequisites for success in overhead costs management. The paper examines the situation in seven industries represented in the sectors of manufacturing and transportation/storage for the time period from 2008 to 2017. The paper concludes with several recommendations for academia, businesses, and future research.
Keywords: D23; O14; O33; 330; digitalization; organizational behaviour; overhead-costs management